Commodification of Culture: Selling India - Kuršataitė, Lolita (Acta Orientalia Vilnensia, 2004)
The aim of this paper is to summarise recent ideas regarding commodification of culture and to take a brief look into various forms of this process in India, especially those related to tourism, and we discuss the views of K. Meethan and R. Shepherd. This issue involves a discussion about the concept of authenticity (“authentic culture”, “authentic past”) as well as homogenisation and heterogenisation of culture in relation to tourism: nations and localities are attempting to present themselves as different, possessing singular qualities of space and culture, and this also provides the means by which the sense of national or local identity can be constructed. Seeing tourism as a series of spatial narratives, semiotics was chosen as a methodological tool for this brief analysis. The main themes of Indian culture for sale are outlined: glorious past, spirituality and the mysterious land of Secret.